"After reading this article you should be able to ..." / Vasudevan Subrahmanyam (Universiti Teknologi MARA, Terengganu, 1991)
This article discusses the importance of having clearly defined explicit instructional objectives (ElOs) for learning situations so as to enable the learner to understand what he is expected to achieve at the end of the learning experience. This will not only make the learning process more meaningful but ensure a greater rate of success. The article also explains specific components of instructional objectives which should be included when writing ElOs.